APPLICATION OF THE 5E EDUCATIONAL MODEL IN TEACHING COMPLEX TOPICS IN THE 7TH GRADE GEOGRAPHY COURSE “CONTINENTS AND OCEANS” (Universal International Scientific Journal, 2026)
The article discusses the theoretical foundations of the 5E educational model (Engage, Explore, Explain, Elaborate, Evaluate) and the methodology for its application in teaching complex topics in the 7th grade geography course “Continents and Oceans”. The research analyzed the impact of lessons organized on the basis of this model on the level of students' mastery of geographical knowledge, critical thinking and practical skills. The results of the experimental test showed that teaching based on the 5E model is more effective than the traditional approach.
Keywords: 5E model, geography education, continents and oceans, constructivism, active learning, innovative methods.